EFFECT OF COLD-ROLLING ON THE ELASTIC PROPERTIES OF (AL2O3)P-AL COMPOSITE - LEE, JC; SUBRAMANIAN, KN (CHAPMAN HALL LTD, 1993)
Mechanical shaping of an aluminium alloy reinforced with Al2O3 particulates, (Al2O3)p-Al, was carried out-by a cold rolling operation. Rolling was performed unidirectionally in a direction perpendicular to the extrusion direction of the composite, until edge cracks formed. Cold rolling was found to cause particulate cracking and interfacial debonding, as well as the redistribution of (Al2O3)p. These parameters have significant roles in determining the elastic properties of the resultant composite.
Keywords: METAL-MATRIX COMPOSITES; POROSITY; MODULUS